Prevalence of anxiety, depressive and insomnia symptoms among the different groups of people during COVID-19 pandemic: An overview of systematic reviews and meta-analyses - Zou, Qi; Tang, Yuning; Jiang, Cheng; Lin, Pengyang; Tian, Jinhui; Sun, Shougang (Frontiers in Psychology, 2022)
Since the pandemic of the novel 2019 coronavirus disease (COVID-19), in addition to the harm caused by the disease itself, the psychological damage caused to the public by the pandemic is also a serious problem. The aim of our study was to summarize the systematic reviews/meta-analyses (SRs/MAs) of the prevalence of anxiety, depression and insomnia in different populations during the COVID-19 pandemic and to qualitatively evaluate these SRs/MAs. We searched the Cochrane Library, PubMed and Web of Science to obtain SRs/MAs related to anxiety, depression, and insomnia in different populations during the COVID-19 pandemic. The main populations we studied were healthcare workers (HCWs), college students (CSs), COVID-19 patients (CPs), and the general populations (GPs). A subgroup analysis was performed of the prevalence of psychological disorders. A total of 42 SRs/MAs (8,200,330 participants) were included in calculating and assessing the prevalence of anxiety, depression, and insomnia in these populations. The results of subgroup analysis showed that the prevalence of anxiety in different populations were: HCWs (20–44%), CSs (24–41%), CPs (15–47%), and GPs (22–38%). The prevalence of depression were: HCWs (22–38%), CSs (22–52%), CPs (38–45%), and GPs (16–35%), statistically significant differences between subgroups (p < 0.05). The prevalence of insomnia were: HCWs (28–45%), CSs (27–33%), CPs (34–48%), and GPs (28–35%), statistically significant differences between subgroups (p < 0.05). The comparison revealed a higher prevalence of psychological disorders in the CP group, with insomnia being the most pronounced. The methodological quality of the included SRs/MAs was then evaluated using AMSTAR 2 tool. The results of the methodological quality evaluation showed that 13 SRs/MAs were rated “medium,” 13 were rated “low,” and 16 were rated “very low.” Through the subgroup analysis and evaluation of methodological quality, we found a higher prevalence of insomnia than anxiety and depression among the psychological disorders occurring in different populations during the pandemic, but the sample size on insomnia is small and more high-quality studies are needed to complement our findings.